2019
DOI: 10.2337/db19-1754-p
|View full text |Cite
|
Sign up to set email alerts
|

1754-P: Follistatin-Like Protein 1 (FSTL1) Plays an Important Role in Human Primary Adipocyte Metabolism

Abstract: Objective: FSTL1, an extracellular glycoprotein, is a novel myokine that is secreted by skeletal muscle. However, its functions in metabolism remain unclear, Adipose tissue is one of the important organs for maintaining energy homeostasis. FSTL1 is known to induce inflammatory response and inhibit insulin-mediated Akt signaling pathway, we aimed to investigate whether FSTL1 play metabolic roles in human adipose tissue. We hypothesized that FSTL1 increases lipolysis through its putative receptor DIP2A (Disco in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…FSTL1 can bind to the myocardial cell membrane through disco interacting protein 2 homolog A (DIP2A) to activate the protein kinase B (Akt) signaling pathway [23]. Recently, Ahn et al [24] observed that FSTL1 mediated lipolysis through the DIP2A receptor in adipocytes. Insulin generally regulates glucose through the phosphatidylinositol-4,5-bisphosphate3-kinase/Akt pathway in adipocytes [22].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…FSTL1 can bind to the myocardial cell membrane through disco interacting protein 2 homolog A (DIP2A) to activate the protein kinase B (Akt) signaling pathway [23]. Recently, Ahn et al [24] observed that FSTL1 mediated lipolysis through the DIP2A receptor in adipocytes. Insulin generally regulates glucose through the phosphatidylinositol-4,5-bisphosphate3-kinase/Akt pathway in adipocytes [22].…”
Section: Discussion/conclusionmentioning
confidence: 99%